PERADILAN AGAMA SEBAGAI LEMBAGA PENEGAK HUKUM ISLAM DI INDONESIA - Azizah Yasmin; Hurriyah Aqilah Ramadhoifah; Aura Rista Afifah (Sriwijaya Journal of Private Law, 2024)
The Religious Courts in Indonesia as Islamic law enforcement institutions have a structured format to ensure justice in resolving family and religious cases. This includes religious judges, clerks and administrative officers, designed in accordance with legislation specifically related to Islamic law, making the process in accordance with the principles of the Koran and hadith. Religious judges play a central role as interpreters of Islamic law. Religious court decisions are not only based on legal facts, but also consider human values and morality in accordance with Islamic law. Religious courts are not only a dispute resolution forum, but also a place for mediation to achieve justice. Alternative methods such as mediation are becoming an integral part of the religious justice format, offering solutions that are in line with Islamic values and promoting constructive dialogue. This process allows for a fair and dignified resolution, while maintaining harmony in society. The importance of enforcing Islamic law through religious courts is not only in the context of justice, but also as a form of respect for religious diversity in Indonesia. Its structured format and detailed explanations reflect the religious courts' commitment to maintaining integrity, justice and social harmony in a multicultural society and diverse beliefs. This research aims to analyze the position and authority in the religious justice structure in terms of statutory regulations. The research uses normative legal research. The approach used is a statutory regulation approach. The legal materials used consist of primary legal materials, secondary legal materials and tertiary legal materials. Data analysis was carried out qualitatively. The role of the Religious Courts is to regulate the traffic of case examinations in courts within the scope of the Religious Courts. Judicial power is a fundamental power as a pillar of power which has the function of upholding justice without the participation of other powers. The authority of religious courts concerns two things, namely relative authority and absolute authority.